Concurrent hyphema and orbital apex syndrome following herpeszoster ophthalmicus in a middle aged lady - Othman, Khairuddin; Tai, Evelyn Li Min; Mohd Noor, Raja Azmi; Muhammed, Julieana; Ahmad Tajudin, Liza Sharmini; John, Tharakan; Muhd Besari, Alwi; Embong, Zunaina; Ismail, Shatriah (Elsevier, 2017)
INTRODUCTION: Hyphema and orbital apex syndrome occurring concurrently in a patient with herpeszoster ophthalmicus have not been reported previously. We present a case with these unique findingsand discuss the pathogenesis of these conditions and their management.PRESENTATION OF CASE: A 59-year-old Malay lady with underlying diabetes mellitus presented withmanifestations of zoster ophthalmicus in the left eye. Two weeks later, she developed total hyphema,and complete ophthalmoplegia suggestive of orbital apex syndrome. She was treated with combinationof intravenous acyclovir and oral corticosteroids, and regained full recovery of ocular motility. Totalhyphema persisted, and she required surgical intervention.DISCUSSION: Hyphema is postulated to occur due to an immune vasculitis affecting the iris vessels. Orbitalapex syndrome is probably due to an occlusive vasculitis affecting the vasculature of the extraocular mus-cles and optic nerve, resulting from a direct invasion by varicella zoster virus or infiltration of perivascularinflammatory cells. Magnetic Resonance Imaging of the brain is essential to exclude possibility of localcauses at the orbital apex area.CONCLUSION: Herpes zoster ophthalmicus is an uncommon ocular presentation. Managing two concur-rent complications; persistent total hyphema and orbital apex syndrome is a challenging clinical situation.Early diagnosis and prompt treatment are essential to prevent potential blinding situation.